Sampled-Data-Based Local Stability of Neutral Time-Delay Systems With Actuator Saturation - Dapeng Li; Shuiqing Ye; Chao Ge (IEEE Access)
In this work, the local stability issue of neutral delay system with actuator saturation under sampled-data controller is studied. Firstly, considering the influence of actuator saturation on the system, the sampled-data controller with variable sampling period is designed by using the input delay method, which can ensure the closed-loop neutral system to achieve local stability. Then, we combine polytopic method to conduct saturated nonlinear part, which is characterized by a convex combustion of state feedback and auxiliary delay feedback. By making full use of sampling information, the less conservative stability condition is given in the form of linear matrix inequalities (LMIs). In addition, the attraction of domain (DA) is also optimized. The proficiency and merits of the suggested method are demonstrated via a numerical example in the end.